2021
DOI: 10.2174/1871520621666210112123528
|View full text |Cite
|
Sign up to set email alerts
|

One Pot Green Synthesis of Doxorubicin and Curcumin Loaded Magnetic Nanoparticles and Cytotoxicity Studies

Abstract: Background: Green synthesis, an alternative method for synthesizing nanoparticles, is cheaper, environmentally friendly, and does not produce toxic effects. Doxorubicin is a chemotherapeutic agent used in lung cancer. Curcumin is a bioactive compound with properties such as an anticancer obtained from Curcuma longa. Objective: This study’s objective was to develop Doxorubicin and Curcumin loaded magnetic nanoparticles that could be synthesized by green tea leaves and investigate cytotoxic effects against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…From studies invoving one-pot synthesis of doxorubicinsilica [22][23][24][25][26][27] and other classes of nanoparticles, [28][29][30] it can be predicted that functional groups of the drug can react with precursors of bioactive glass. Precursors of bioactive glass like tetraethoxysilanes on getting hydrolyzed to subunits of silicon oxides can react with hydroxyl groups of doxorubicin thus allowing incorporation of the same during different stages of the growth of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…From studies invoving one-pot synthesis of doxorubicinsilica [22][23][24][25][26][27] and other classes of nanoparticles, [28][29][30] it can be predicted that functional groups of the drug can react with precursors of bioactive glass. Precursors of bioactive glass like tetraethoxysilanes on getting hydrolyzed to subunits of silicon oxides can react with hydroxyl groups of doxorubicin thus allowing incorporation of the same during different stages of the growth of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the scientific literature presents few reports regarding the fabrication of magnetic iron oxides nanoparticles through green synthesis approach with anticancer potential against lung cancer [ 21 , 22 , 23 ]. No study has previously reported the use of basil as plant material for MNPs’ biosynthesis, whereas only one study reports the MNPs’ biosynthesis using green tea extract, as well as the cytotoxic effect of this MNPs against A549-luc-C8 non-small lung cancer line [ 24 ]. However, in that study [ 22 ], the authors did not investigate the cytotoxic effect of naked MNPs (obtained as such from green synthesis), they loaded the MNPs obtained with doxorubicin and curcumin and afterwards, the cytotoxic effect of the nanoformulation against NSCLC line was investigated.…”
Section: Introductionmentioning
confidence: 99%